A Simple and Effective Method to Evaluate Peak Flowmeters - Liman Wang; Melva Proudlock; Mingyao Liu (Canadian Respiratory Journal)
OBJECTIVE: Peak flowmeters have been widely used to monitor the course of asthma. The objective of this study was to develop a simple, convenient and effective method to evaluate these devices routinely.